Estudo da influência de sistemas microemulsionados na molhabilidade de arenitos e na recuperação avançada de petróleo - Firmino, Priscilla Cibelle Oliveira de Souza (2016)
Sandstone-type reservoir rocks are commonly responsible for oil accumulation. The wettability is an important parameter for the physical properties of the container, since it interferes in characteristics such as relative permeability to the aqueous phase, residual oil distribution in the reservoir, operating characteristics with waterflood and recovery of crude oil. This study applied different types of microemulsion systems - MES - in sandstone reservoirs and evaluated their influences on wettability and residual oil recovery. For this purpose, four microemulsion were prepared by changing the nature of ionic surfactants (ionic and nonionic). Microemulsions could then be characterized by surface tension analysis, density, particle diameter and viscosity in the temperature range 30° C to 70° C. The studied oil was described as light and the sandstone rock was derived from the Botucatu formation. The study of the influence of microemulsion systems on sandstone wettability was performed by contact angle measurements using as parameters the rock treatment time with the MES and the time after the brine surface contact by checking the angle variation behavior. In the study results, the rock was initially wettable to oil and had its wettability changed to mixed wettability after treatment with MES, obtaining preference for water. Regarding rock-MES contact time, it was observed that the rock wettability changed more when the contact time between the surface and the microemulsion systems was longer. It was also noted only a significant reduction for the first 5 minutes of interaction between the treated surface and brine. The synthesized anionic surfactant, commercial cationic, commercial anionic and commercial nonionic microemulsion systems presented the best results, respectively. With regard to enhanced oil recovery performance, all systems showed a significant percentage of recovered oil, with the anionic systems presenting the best results. A percentage of 80% recovery was reached, confirming the wettability study results, which pointed the influence of this property on the interaction of fluids and reservoir rock, and the ability of microemulsion systems to perform enhanced oil recovery in sandstone reservoirs.